IMPACT OF VALUE-ADDED TAX ON GROSS DOMESTIC PRODUCT OF BANGLADESH - Jewel, Jafrul Shahriar (Indian Journal of Finance and Banking, 2022)
International Monetary Fund advocates the Bangladesh government introduce Value Added Tax that was incepted in 1991. Before that, it was known as sales tax. Now Bangladesh scales up its country income status from a low-income country to a middle-income country, while value-added tax is the key player contributing a great part to gross domestic product. The study inspects the effect of value-added tax on Bangladesh’s gross domestic product using a long dataset from 1991-1992 to 2020-2021. The study uses a co-integration technique invented by Johansen with a restricted V.A.R. named vector error correction model. This article finds that value-added tax has a specific positive impact on a gross domestic product that ensures good and continuous economic growth over the decades in Bangladesh. JEL Classification Codes: K34.